Investigation of the wear progression of nozzle in abrasive waterjet machining with different abrasive material - Lusi, Nuraini; Gebremariam, Mebrahitom; Alao, Abdur-Rasheed; Saptaji, Kushendarsyah; Azmir, Azhari (J. E. Purkyne University in Ústí nad Labem, 2025)
Determining the productivity and quality of precision AWJ machining requires routine and careful inspection of nozzle condition. The degradation of the inner bore of the nozzle adversely impacts the mixing efficiency and uniformity of the water jet, thereby affecting its cutting performance. In this study, new nozzle was designed and manufactured using additive manufacturing and were made of 316 L stainless steel. The new nozzle consists of two combined parts with the peculiarity of being easy to install using a screw thread. The wear behavior of the new nozzle was examined using an accelerat-ed wear test. An accelerated wear test was conducted on the hard abrasive silicon carbide (SiC) and compared to garnet, the abrasive commonly used in the AWJ industry. The aim of the test was to de-termine the wear pattern of the nozzle. The cumulative mass loss and nozzle diameter increase for different abrasives were measured. The geometric change in the nozzle is made visible through de-structive examination. The findings indicated that the type of abrasives significantly affects nozzle wear. As the hardness of the abrasive increases, the diameter of the nozzle enlarges, resulting in accel-erated nozzle wear. The mass loss factor of SiC abrasives is three times higher than that of garnet abrasives. This research allows practitioners to monitor the nozzle wear behaviour during the AWJ process. The results obtained were used to estimate the nozzle life based on the observed wear history.